2018
DOI: 10.1002/pon.4748
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of health care services in cancer patients with elevated fear of cancer recurrence

Abstract: Cancer patients with clinical levels of FCR are more likely to consult health care providers and to use psychotropic medications, which may translate into significant costs for society and the patients themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 29 publications
(101 reference statements)
3
76
2
Order By: Relevance
“…In survivors of adult cancer, maladaptive health behaviors (e.g., repeated medical visits for reassurance-seeking) are correlated with and considered as adverse outcomes of FCR. 4 Parents likely instigate these medical visits for their child, and thus the child's healthcare utilization will likely be moderated through their parents' FCR.…”
Section: Parent/child Relationshipmentioning
confidence: 99%
“…In survivors of adult cancer, maladaptive health behaviors (e.g., repeated medical visits for reassurance-seeking) are correlated with and considered as adverse outcomes of FCR. 4 Parents likely instigate these medical visits for their child, and thus the child's healthcare utilization will likely be moderated through their parents' FCR.…”
Section: Parent/child Relationshipmentioning
confidence: 99%
“…In addition, from a public health standpoint, FCR is related to increased health-care utilization and costs (15, 16). In a recently published study, FCR was the most distressful and commonly reported problem by patients with breast cancer (17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] At the system level, clinical FCR is associated with increased health-care costs. [6][7][8] Research on FCR is growing rapidly, with increasing data on its prevalence, correlates and treatment across cancer types. 2,9 Efforts to systematically capture FCR have been hampered by a lack of agreement regarding a gold standard measure and use of miscellaneous assessment tools of variable quality.…”
Section: Introductionmentioning
confidence: 99%